Landslide Mechanisms in the Cisumdawu Toll Road through a Geoforensics Approach to Increase Slope Stability - Mardjuni, Adhystira; Pramono Rahardjo, Paulus; Aldiamar, Fahmi (UKaRsT, 2025)
Landslides are a significant threat to infrastructure in tropical regions like Indonesia, especially in projects that cross volcanic slopes. A significant case occurred on the Cisumdawu Toll Road Section 2, triggered by high rainfall and water-saturated young volcanic soil. Given the complexity of such failures, comprehensive investigations are crucial. This study aims to analyze the causes and mechanisms of landslides in the Ciherang Village, specifically at STA 19 KM 65 using a geoforensics approach. This approach involves field investigations to collect geotechnical and geophysical data such as boring logs, SPT, pressure meters, inclinometers, and geoelectric resistivity testing. These were used to reconstruct subsurface conditions before failure. Numerical modeling was then performed with variations in groundwater level (GWL) and K₀ to simulate slope stability and identify failure triggers. The results show that landslides was translational, occurring in the transition zone between sandy silt (tuff) and weathered tuff breccia layers at depths of 30–35 meters, where differences in permeability made the zone vulnerable. The decrease in GWL significantly improved slope stability, increasing the safety factor to 1.435, while K₀ variation had a lesser impact. A combination of bored piles, ground anchors, soil nailing, and slope regrading effectively stabilized the slopes. These findings contribute to a better understanding of the mechanisms and causes of landslides so that mitigation strategies can be more targeted to increase slope stability.